Stealing land in the name of religion: A Rastafari religio-political critique of land theft by global imperial forces - Hewitt, Roderick R. (HTS teologiese studies, 2016)
The issue of land has been central to Rastafari origins and ideological construct. Ethiopia, Africa, Babylon, Zion and Jamaica are symbols that point not only to physical location but also their ideological and psychological identity formation. This article uses Rastafari hermeneutics to critique the phenomenon of African Jamaican uprooting and dispossession of and from their land by powerful and global conglomerate forces that use the instrument of politics, economic and religion to accomplish their agenda. This article uses the Rastafari theological reflections, a theoretical framework that employs the phenomenon of faith, tradition and experience to interrogate the phenomenon of displacement of people through land theft. The religio-political narrative of Jamar Rolando McNaughton Jr, a young Jamaican reggae artist popularly known by his stage name Chronixx, will serve as the principal lens through which to interrogate the phenomenon of landlessness among the poor, primarily within the Jamaican context.